The Role of TLR4 in Lung Epithelial Cell Injury Caused by Influenza Virus Combined with Staphylococcus aureus - Bei Chen; Chunjing Chen; Fangguo Lu; Xiaoqi Wang; Xianggang Zhang; Zhibin Wang; Huihui Liu (Microorganisms)
Influenza A virus (IAV) is a major cause of respiratory illness in humans and animals. Secondary bacterial infections, especially those caused by Staphylococcus aureus (SA), significantly increase influenza-related morbidity and mortality. However, the mechanisms underlying these co-infections remain unclear. In this study, we examined how IAV infection influences SA-induced inflammation in lung epithelial cells. Our study was conducted based on in vitro experiments. First, we infected MLE-12 cells with IAV, confirming viral replication and the resulting cell damage. SA was then introduced 24 h or 36 h post-infection, and the cellular responses were measured. We assessed cell viability, cell-free DNA, Citrullinated histone H3, and the mRNA expression of TLR4 and proinflammatory cytokines. Our results showed that IAV+SA stimulation significantly increased upregulated TLR4 expression and inflammatory damage. To further explore TLR4’s role, we used the inhibitor TAK-242 and a TLR4 siRNA knockdown. Both approaches reduced the inflammatory response triggered by IAV and SA stimulation. These findings suggest that TLR4 is a key mediator in the enhanced inflammation observed during IAV and SA co-infection, offering a potential target for therapeutic intervention.